Gender and attitudes towards English varieties: Implications for teaching English as a global language. (August 2018) - Chan, Jim Yee Him
Abstract: The study reported in this paper adopted both direct (a large-scale questionnaire survey) and indirect (a verbal-guise test) measures to investigate gender differences in second language (L2) learners' attitudes towards different English varieties in secondary schools in Hong Kong. The investigation considered various factors affecting students' attitudes to language including their affective feelings, cultural identity, awareness of language variations, experience of language use, perceived intelligibility of English accents and, more importantly, situational language choices. Consistent with previous studies, the findings suggest that the female learners were more positively oriented towards native speaker (NS) pronunciation and tended to adopt it as their teaching model and learning target; they also had greater confidence than males in their ability to understand British English pronunciation. However, their greater sensitivity to NS standards was found to be limited to high-stakes English-speaking contexts. In contrast, male learners had greater tolerance or acceptance of local pronunciation. This paper concludes by discussing the implications of L2 learners' gender differences in attitudes for English language education and the design of English language teaching materials and assessments.